Open access in the age of a pandemic. Issue 1 (22nd October 2020) - Alemneh, Daniel Gelaw; Hawamdeh, Suliman; Chang, Hsia‐Ching; Rorissa, Abebe; Assefa, Shimelis; Helge, Kris
Abstract: The COVID‐19 pandemic highlighted the importance of transparency, open, and timely access to information. Open Access (OA) has the potential to increase the exposure and use of not only published research but also authoritative and reliable information. The Coronavirus (COVID‐19) impacted the work of journalists, scientists, and doctors while ordinary citizens are seeking trusted information sources and the truth about the new virus. Government and private institutions worldwide are reacting to the new situation where researchers, educators, students, and staff are trying to adjust to remote teaching and learning as well as telecommuting. In March 2020, a message from the White House was sent to the Scholarly Publishing Community asking them to make all COVID‐19 papers openly available and machine readable. Considering the evolving and unresolved issues around OA and scholarly communications, together with the UN 2030 Agenda (a plan of action for sustainable, universal development), this panel brings together diverse perspectives to review the current landscape of OA and shed light on the role it plays in such crises. The panel will also discuss the future implications and impact of the pandemic in the overall advancement of scholarship in general.